1993
DOI: 10.1182/blood.v82.3.830.830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three candidate mutations causing type IIA von Willebrand disease using a rapid, nonradioactive, allele-specific hybridization method

Abstract: Type IIA von Willebrand disease (vWD), the most common type II vWD variant, is characterized by decreased binding of von Willebrand factor (vWF) to platelet glycoprotein Ib (Gplb) and by a decrease in large and intermediate vWF multimers. Mutations reported to cause vWD type IIA are clustered within the A2 domain of vWF, which is encoded by exon 28. Genomic DNA from affected members of 12 unrelated families with type IIA vWD were screened for these mutations by a rapid, nonradioactive, allele-specific oligonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A 936 Table 1 Phenotypic and genotypic data on the 17 kindreds with a discrepant VWF: activity/VWF: antigen ratio bp fragment of the 5' region of the exon 28 that encoded for the VWF-A1 domain was amplified by polymerase chain reaction (PCR). The primer sequences were 5'-TGGGAATATGGAAGTGCATTG-3' and 5'-CCGATCC-TTCCAGGACGAAC-3' (18). The PCR products were purified using the QIAmp DNA purification kit (Qiagen Ltd.).…”
Section: Genetic Analysismentioning
confidence: 99%
“…A 936 Table 1 Phenotypic and genotypic data on the 17 kindreds with a discrepant VWF: activity/VWF: antigen ratio bp fragment of the 5' region of the exon 28 that encoded for the VWF-A1 domain was amplified by polymerase chain reaction (PCR). The primer sequences were 5'-TGGGAATATGGAAGTGCATTG-3' and 5'-CCGATCC-TTCCAGGACGAAC-3' (18). The PCR products were purified using the QIAmp DNA purification kit (Qiagen Ltd.).…”
Section: Genetic Analysismentioning
confidence: 99%
“…The G(5075)->A, detected in patient T5 with type 2A vWD, is a transition substituting amino acid Gly 1609 with Arg. Although the same transition has been found in Caucasians (20,21), there is no proof that this transition is a cause of type 2A vWD since expression experi ments have not been performed. The sequence of this mutant was con sistent with that of the pseudogene.…”
Section: Discussionmentioning
confidence: 78%
“…Of the transitions identified in the present study, the R1597W detected in patients T2 and T3 is the most frequent among reported type 2A vWD transitions (8,(16)(17)(18) and belongs to group II (14,15). The amino acid substitution R1597Q, detected in patient T4 with type 2A vWD, has also been identified else where (8,19,20), but no expression studies have been conducted. The G(5075)->A, detected in patient T5 with type 2A vWD, is a transition substituting amino acid Gly 1609 with Arg.…”
Section: Discussionmentioning
confidence: 99%